2005
DOI: 10.1007/s00170-004-2241-1
|View full text |Cite
|
Sign up to set email alerts
|

Integration of dynamic behaviour variations in the stability lobes method: 3D lobes construction and application to thin-walled structure milling

Abstract: Gilles Cazenave-Larroche. Integration of dynamic behaviour variations in the stability lobes method: 3D lobes construction and application to thinwalled structure milling. International Journal of Advanced Manufacturing Technology, Springer Verlag, 2006, vol. 27, pp. 638-644. 10 Integration of dynamic behaviour variations in the stability lobes method: 3D lobes construction and application to thin-walled structure millingAbstract Vibratory problems occurring during peripheral milling of thin-walled structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 11 publications
0
44
0
1
Order By: Relevance
“…Regarding the errors, little has been said about the uncertainty in the stability diagrams although several authors have recognized some inaccuracies [38]. Thevenot et al [35] studied the influence of some input parameters on the stability diagram, showing that the critical parameter is the modal frequency of the system. For the method proposed here, the main sources of error in the stability diagram calculation come from the modelling of the process, the tool-path discretization and the input parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the errors, little has been said about the uncertainty in the stability diagrams although several authors have recognized some inaccuracies [38]. Thevenot et al [35] studied the influence of some input parameters on the stability diagram, showing that the critical parameter is the modal frequency of the system. For the method proposed here, the main sources of error in the stability diagram calculation come from the modelling of the process, the tool-path discretization and the input parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This work assumes the methodology originally proposed for thin walls milling by Thevenot et al [35], but a different stability diagram is proposed. The method follows these steps:…”
Section: Calculation Of Stable Spindle Speeds For Thin Floors Millingmentioning
confidence: 99%
See 1 more Smart Citation
“…In these zones, the part was able to be modelled with constant dynamic properties and with rigid body motion [12]. The stability lobe change during machining that lead to a third dimension on the stability lobe [13,14]. This approach was also extended by taking into account machine and tool flexibility [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the machining process of thin-walled structure, it can be observed that the dynamic behaviour of the tool workpiece system depends on the tool position in the workpiece. This phenomenon and the problem of the influence of several modes on stability lobes are discussed in [36]. On the other hand, modal interaction can affect surface roughness in milling thin-walled structures [33].…”
Section: Introductionmentioning
confidence: 99%